A RARE CAUSE OF PAIN IN THE MUSCULOSKELETAL SYSTEM: BONE MARROW EDEMA SYNDROME - DAĞDEVIREN, ONUR; TÜRKKAN, EMINE; DAĞ, HÜSEYIN; BAYRAKTARLI, RECEP YILMAZ (Innovare Journal of Medical Sciences, 2021)
Bone marrow edema syndrome is characterized by increased interstitial fluid in the bone marrow and is a rare disease in children and adolescents. Therefore, to make this diagnosis, it should be considered in the differential diagnosis of musculoskeletal system pain. With this perspective, the aim was to present a 17-year-old patient who was diagnosed on magnetic resonance imaging with bone marrow edema and to highlight characteristics of this rare condition in the pediatric and adolescent population.